2009
DOI: 10.1017/s0317167100007095
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Concise QOL Questionnaire for Brain Tumor Patients

Abstract: 340Clinical studies in neuro-oncology typically express results using traditional outcome measures such as tumor size, toxicity effects, and of course, survival rates. Although paramount, these measures fail to fully capture the residual capacity, psychosocial health, and overall quality of life (QOL) of surviving patients. In recent years, a new emphasis has been placed on evaluating quality of life in patients, thus acknowledging the impact produced not only by the disease process, but also by different ABST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Ever since the publication of important functional studies such as the brain maps acquired by Ojemann et al in 117 epilepsy patients and showing a great variability in the speech localization, a greater emphasis has been placed on the study of the function, thereby realizing that reliance on topographical anatomy alone is inadequate 54 . Moreover, studies in neuro-oncology are now included as an integral facet of the evaluation of patients quality of life data as well as neuro-cognitive evaluations, leaning toward a more inclusive and integrated view of the patient as an individualwhole [55][56][57] . The concept of brain functioning now involves a dynamic organization of networks connecting several cortical and subcortical areas of the brain 1,58 .…”
Section: Discussionmentioning
confidence: 99%
“…Ever since the publication of important functional studies such as the brain maps acquired by Ojemann et al in 117 epilepsy patients and showing a great variability in the speech localization, a greater emphasis has been placed on the study of the function, thereby realizing that reliance on topographical anatomy alone is inadequate 54 . Moreover, studies in neuro-oncology are now included as an integral facet of the evaluation of patients quality of life data as well as neuro-cognitive evaluations, leaning toward a more inclusive and integrated view of the patient as an individualwhole [55][56][57] . The concept of brain functioning now involves a dynamic organization of networks connecting several cortical and subcortical areas of the brain 1,58 .…”
Section: Discussionmentioning
confidence: 99%
“…47 Furthermore, pain is rated as an important quality of life concern for neuro-oncology patients, as evidenced by recent studies on patient well-being. [48][49][50][51][52] Together these findings advocate for expending greater efforts in the battle against postcraniotomy pain. Interestingly, a study conducted by Stoneham and Walters 53 revealed that opiophobia among neuroanesthetists constitutes a continuing barrier to the ultimate resolution of postoperative pain.…”
Section: Distinguishing Surgical From Brain Tumor Headachesmentioning
confidence: 86%
“…To assess QOL, patients filled out the Sherbrooke NeuroOncology Assessment Scale (SNAS), a recently developed and validated QOL questionnaire that assess both core and disease-specific issues relevant to neuro-oncology patients 14 . The SNAS is a 30 item questionnaire composed of seven multi-item scales: (1) functional wellbeing, (2) symptom severity/fear of death, (3) social support/acceptance of disease, (4) autonomy in personal care, (5) digestive symptomatology, (6) neurocognitive function, and (7) pain.…”
Section: Quality Of Life Questionnairementioning
confidence: 99%